Species-Area Relationships Induced by Forest Habitat Fragmentation Apply Even to Rarely Detected Organisms. (June 2021) - Palmeirim, Ana Filipa; Fraga, Rafael de; Vieira, Marcus V.; Peres, Carlos A.
Neotropical snakes have extremely low detection rates, hampering our understanding of their responses to habitat loss and fragmentation. We addressed this gap using a limited sample (50 individuals, 16 species) across 25 variable-size insular forest fragments within a hydroelectric lake and four adjacent mainland continuous forest sites, in Central Brazilian Amazonia. The number of species recorded on forest islands (1.55± 0.78) was much lower than that at continuous forest sites (5.0± 3.1), with no snakes being recorded at twelve islands smaller than 30 ha. As such, snake assemblages were positively affected by forest area, explaining 48% of the number of species, and negatively affected by island isolation. The markedly higher number of species recorded across continuous forest sites likely results from the availability of riparian habitats, which have virtually disappeared from the archipelagic landscape given the widespread inundation of lowland areas. To prevent further severe biodiversity loss, including those of poorly known rare taxa, conservation policies should avert the additional construction of mega-dams that create myriad of small islands, in addition to extensive reservoir lakes from which all riparian habitats are eliminated.